(untitled) (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted on aqueous extracts of leaves of some herbal plants viz., Beleric myrobalan; bohera (Terminalia belirica), Chebulic myrobalan; horitoki (Terminalia chebula), Sweet basil; tulsi (Ocimum gratissmum) and arjunaa myrobalan; arjun (Terminalia arjuna) for investigating the presence of biologically active substance. The seeds of two vegetable crops such as, swamp cabbage (Impoea aquatica) and okra (Hibiscus esculentus) were tested for germination and seedling growth treating with aqueous extract of four herbal plant leaves. The chemical investigation on effective plant extract was also attempted. The aqueous extract of bohera leaves increased germination of seeds tested and enhanced the growth of shoot length and root length of swamp cabbage (Impoea aquatica) and okra (Hibiscus esculentus) whereas the aqueous extract of horitoki significantly reduced and delayed germination, growth of shoot length and root length of swamp cabbage seeds compared with control; water. The maximum germination was in okra and swamp cabbage seeds within 5 and 4.8 days respectively, treated with the leaves extract of bohera. Shoot lengths were 16.2 and 16.43 cm and root length were 8.74 and 8.91 cm for okra and swamp cabbage seedlings, respectively. The aqueous extract of horitoki showed the lowest rate and late germination at 6 and 5.8 days and minimum shoot lengths were 13.13 and 13.36 cm, and root lengths were 5.91 and 6.08 cm for okra and swamp cabbage seedlings, respectively. The thin layer chromatography (TLC) examination of chloroform extract of bohera leaves showed four distinct compounds at Hexane: Ethyl acetate (3:1, v/v) while horitoki leaves showed three distinct compounds at Hexane: Ethyl acetate (5:1, v/v). DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11569 J. Environ. Sci. & Natural Resources, 5(1): 141-150, 2012